Bacterial and fungal communities in indoor aerosols from two Kuwaiti hospitals - Habibi, Nazima; Uddin, Saif; Behbehani, Montaha; Al Salameen, Fadila; Razzack, Nasreem Abdul; Zakir, Farhana; Shajan, Anisha; Alam, Faiz (Frontiers in Microbiology, 2022)
The airborne transmission of COVID19 has drawn immense attention to bioaerosols. The topic is highly relevant in the indoor hospital environment where vulnerable patients are treated and healthcare workers are exposed to various pathogenic and non-pathogenic microbes. Knowledge of the microbial communities in aerosol will enable precautionary measures to prevent any hospital infection outbreak and better assess occupational exposure of the healthcare workers. This study presents a baseline of the bacterial and fungal population of two major hospitals in Kuwait dealing with COVID patients, and in a non-hospital setting through targeted amplicon sequencing. The predominant bacteria of bioaerosols were Variovorax (9.44%), Parvibaculum (8.27%), Pseudonocardia (8.04%), Taonella (5.74%), Arthrospira (4.58%), Comamonas (3.84%), Methylibium (3.13%), Sphingobium (4.46%), Zoogloea (2.20%), and Sphingopyxis (2.56%). ESKAPE pathogens such as Pseudomonas, Acinetobacter and Staphylococcus were also found in lower abundances. The fungi were represented by Wilcoxinia rehmii (64.38%), Aspergillus ruber (9.11%), Penicillium desertorum (3.89%), Leptobacillium leptobactrum (3.20%), Humicola grisea (2.99%), Ganoderma sichuanense (1.42%), Malassezia restricta (0.74%), Heterophoma sylvatica (0.49%), Fusarium proliferatum (0.46%), and Saccharomyces cerevisiae (0.23%). Some common and unique operational taxonomic units (OTUs) of bacteria and fungi were also recorded at each site; this inter-site variability shows that exhaled air can be a source of this variation. The alpha diversity indices suggested variance in species richness and abundance in hospitals than non-hospital sites. The community structure of bacteria varied spatially (ANOSIM r2=0.181-0.243; p >0.05) between the hospital and non-hospital sites, whereas fungi were more or less homogenous. Key taxa specific to the hospitals were Defluvicoccales, fungi, Ganodermataceae, Heterophoma and H. sylvatica compared to Actinobacteria, Leptobacillium, L. leptobacillium and Cordycipitaceae at the non-hospital site (LefSe, FDR q ≤ 0.05). The hospital/non-hospital MD index >1 indicated shifts in microbial communities of indoor air in hospitals.